The circadian based hypertension-management: new approach for better blood pressure goals - Firdaus, Muhammad; Tjahjono, Cholid Tri (Heart Science Journal, 2024)
Hypertension, a primary changeable risk factor for overall mortality, affects approximately 1.4 billion people worldwide, accounting for about 31% of the global adult population. The primary method of diagnosis is through in-office or clinic blood pressure readings, which do not consider the circadian rhythm’s fluctuations. Various homeostatic parameters, including blood pressure, are influenced by circadian rhythms, which follow a day-night cycle. Blood pressure typically decreases at night and rises during the day in line with the circadian rhythm. 24-hour ambulatory blood pressure monitoring offers a more comprehensive evaluation of hypertension. The phenomena of nocturnal blood pressure and the dipping pattern are closely interconnected characteristics that provide comparable therapeutic insights. In hypertensive patients, nighttime blood pressures were found to be a better predictor of cardiovascular and all-cause mortality outcomes than daytime systolic pressures. The current range of anti-hypertensive medications used to manage hypertension reveals that while some have an impact on circadian rhythms, others do not. Existing research on these drugs presents mixed views on the benefits of administering hypertension medication in the morning versus the evening. A significant study, known as the BedMed trial, is currently in progress to assess the cardiovascular effects of administering hypertension medication at bedtime as opposed to the traditional morning administration. This study could potentially provide valuable insights for improved future management of hypertension.